Orangutan mating behavior and strategies - Utami Atmoko, S. Suci; Tatang Mitra Setia; Goossens, Benoit; James, Sheena S.; Knott, Cheryl D.; Morrogh-Bernard, Helen C.; Van Schaik, Carel P. van Schaik; Van Noordwijk, Maria A. (Oxford University Press, 2009)
Orangutans are a species with a very pronounced sexual dimorphism, in that fully grown males are about twice the size of females, but adult, sexually mature males come in two distinct morphs. Unflanged males lack the secondary sexual characteristics (e.g., cheek flanges, throat sack, long call) of the flanged males, but are sexually active, fertile and known to sire offspring. In some males, full development may be delayed until they are over 30. This 'bimaturism' is hypothesized to have arisen as a result of sexual selection in which female choice, male-male competition and male coercion have all played important roles. The data reviewed here show that male-male competition is highly affected by the reproductive condition of the females and female preference for associating with particular males. Potentially reproductive female orangutans are widely dispersed in space and time. Consequently, dominant flanged adult males cannot easily exert permanent control over access to reproductive females.